Mass spectrometry and in situ x-ray photoelectron spectroscopy investigations of organometallic species induced by the etching of germanium, antimony and selenium in a methane-based plasma - Meyer, T; Girard, A; Bouška, Marek; Baudet, Emeline; Baillieul, Marion; Němec, Petr; Nazabal, Virginie; Cardinaud, C (Institute of Physics Publishing Ltd, 2023)
Organometallic positive ions were identified in inductively coupled plasmas by means of mass spectrometry during the etching of Ge, Sb, Se materials. A preliminary study was focused on identifying M (x) H (y) + (M = Ge, Sb, Se) positive ion clusters during a H-2/Ar etching process. The methane addition to the H-2/Ar mixture generates CH (x) reactive neutral species. The latter react with the metalloids within gas phase to form M (x) C (y) H (z) (+) organometallic ions. In addition, the etching of Sb2Se3 and Ge19.5Sb17.8Se62.7 bulk targets forms mixed products via ion-molecule reactions as evidenced by the presence of SeSbC (x) H (y) (+) ion clusters. Changes in surface composition induced by the newly formed organometallic structures were investigated using in situ x-ray photoelectron spectroscopy. In the case of the Ge and Sb surfaces, (M)-M-C (x) environments broadened the Ge 2p(3/2), Ge 3d, Sb 3d and Sb 4d spectra to higher values of binding energy. For the Se surface, only the hydrogen and methyl bonding could explain the important broadening of the Se 3d core level. It was found that the Ge39Se61 thin film presents an induced (Ge)-Ge-Se entity on the Ge 2p(3/2) and Ge 3d core levels.
Hmotnostní spektrometrie a in situ rentgenová fotoelektronová spektroskopie zkoumání organokovových látek indukovaných leptáním germania, antimonu a selenu v plazmatu na bázi metanu
Keywords: mass spectrometry; x-ray photoelectron spectroscopy; organometallics; plasma etching; CH4; mass spectrometry; x-ray photoelectron spectroscopy; organometallics; plasma etching; CH4